Misguided democracy in Malaysia and Indonesia : digital propaganda in Southeast Asia - Nuurrianti Jalli; Ika Idris (Selangor : Strategic Information and Research Development Centre, 2024)
"This book examines the exploitation of the internet for propagating disinformation in Southeast Asia, with an emphasis on Malaysia and Indonesia. It discusses the impact on democratic processes, the difficulties in balancing free speech and disinformation control, and aims to stimulate discourse on digital revolution's influence on our societies"--{u2021}cProvided by publisher.
"Misguided Democracy in Malaysia and Indonesia: Digital Propaganda in Southeast Asia examines the weaponization of the internet in Southeast Asia. Nuurrianti Jalli and Ika Idris meticulously unpack the intricate strategies and tactics used by propagandists, state entities, and political factions to manipulate and mislead public opinion through social media. The topics discussed cover the role disinformation plays in altering electoral behavior, political dialogue, societal unity, regional stability, and global diplomacy. By guiding readers through the convoluted landscape of internet propaganda in Southeast Asia, this book aspires to stimulate thoughtful discourse on the influential role of the digital revolution in molding the future of our societies"--back cover.
1. Understanding propaganda -- 2. Propaganda in the digital era -- 3. Using social media as propaganda battlegrounds in Southeast Asia -- 4. Cyberwarfare and computational propaganda in Malaysia: trends and patterns -- 5. Government propaganda in Indonesia: the burning ambition for a single narrative -- 6. Disinformation narratives in Indonesia and Malaysia.
Bibliography : pages 123-149.
Keywords: Disinformation -- Malaysia; Disinformation -- Indonesia; Propaganda -- Malaysia; Propaganda -- Indonesia; Digital media -- Political aspects -- Malaysia; Digital media -- Political aspects -- Indonesia; Digital media -- Social aspects -- Malaysia; Digital media -- Social aspects -- Indonesia